The Transformative Power of Trust: Exploring Tertiary Desistance in Reinventive Prisons - Ugelvik, Thomas (The British journal of criminology, 2022)
While prisons are often described as places of pain, despair and hopelessness, studies show that some prisoners under certain conditions report positive life changes happening in prison. This paper explores the connections between trust and desistance processes, specifically between the experience of being trusted and ‘tertiary desistance’. I argue that trust can be an engine of positive change in prison and that the experience of being trusted might even acquire additional value from the low-trust and risk-sensitive environment that most prisons normally offer prisoners. Finally, I discuss whether prisons that manage to get this balance right deserve to be called ‘reinventive prisons’.